Radix saw: a useful tool for rhinoplasty to correct high radix - Şeneldir,Süreyya (2021)
Abstract Introduction: The most difficult aspect of radix lowering is determining the maximum amount of bone that can be removed with osteotomes; here, we describe use of a radix saw, which is a new tool for determining this amount. Objective: In this study, we describe use of a radix saw, which is a new tool to reduce the radix. Methods: The medical charts of 96 patients undergoing surgery to lower a high radix between 2016 and 2017 were assessed retrospectively. All operations were performed by the senior surgeon. Outcomes were assessed by comparing preoperative photographs with the most recent follow-up photographs (minimum of 6 months postoperatively). The photographs were all taken using the same imaging settings, and with consistent subject distance and angulation. The photographs were subsequently analysed by authors. Results: The study population consisted of 96 patients (70 women, 26 men) who underwent rhinoplasty between 2016 and 2017. The mean age of the patients was 28.8 years (range: 18-50 years) and the mean clinical follow-up period was 1.8 years. No patient required revision surgery due to radix problems, and there were no cases with unwanted bone fragments or radix asymmetry. The swelling and oedema seen immediately after surgery subsided after an average of 7-10 days. Conclusion: In conclusion, a radix saw can be used for rhinoplasty requiring delicate bone removal in patients with a high radix. Level IV: Evidence obtained from multiple time series with or without the intervention, such as case studies. Dramatic results in uncontrolled trials might also be regarded as this type of evidence.